Energy levels and roughage sources for bulls on 140-day test - M. McKee; K.L. Conway; G. Fink; R.R. Schalles; K.K. Bolsen; K.O. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1975)
Thirty-nine Angus, Hereford, and part Simmental bulls were tested 140 days (December 18, 1973 to May 6,1974) for weight gained. Bulls were divided into four groups and fed four different rations that had been formulated for two energy levels (high and medium) and two sources of roughage (corn silage or oats and prairie hay). Average daily gains (lbs.) on the four rations were: high energy silage, 3.48; high energy oats and prairie hay, 3.27; low energy silage, 2.58; and low energy oats and prairie hay, 3.41.
Keywords: Cattlemen' s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Energy; Roughage; Bulls